2014
DOI: 10.2113/gscpgbull.62.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary successions and palynoevent stratigraphy from the non-marine Lower Cretaceous to the marine Upper Cretaceous of the Nuussuaq Basin, West Greenland

Abstract: The Nuussuaq Basin, West Greenland, comprises the only exposures of Mesozoic sedimentary strata on the west coast of Greenland. The Nuussuaq Basin exposes Cretaceous and Paleocene siliciclastic strata, referred to as the Nuussuaq Group, overlain by volcanic rocks, mainly of Paleocene age, referred to as the West Greenland Basalt Group. Regional seismic studies indicate that the Cretaceous strata of the Nuussuaq Basin may be correlated to the Appat and Kangeq seismic sequences in the offshore basins.The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Some events are coeval, so the 187 bio events define 106 bioevent horizons. Bioevent data are also incorporated from Piasecki (2003) for the Neo gene of offshore West Greenland and from Pedersen & Nøhr-Hansen (2014) for Albian to Paleocene strata of the Nuussaq Basin, West Greenland. In addition to biostratigraphic determinations, palaeoenvironmental inferences are made from the data, using, for example, individual dinocyst species and dinocyst assemblages.…”
mentioning
confidence: 99%
“…Some events are coeval, so the 187 bio events define 106 bioevent horizons. Bioevent data are also incorporated from Piasecki (2003) for the Neo gene of offshore West Greenland and from Pedersen & Nøhr-Hansen (2014) for Albian to Paleocene strata of the Nuussaq Basin, West Greenland. In addition to biostratigraphic determinations, palaeoenvironmental inferences are made from the data, using, for example, individual dinocyst species and dinocyst assemblages.…”
mentioning
confidence: 99%
“…However, an FO in the middle Turonian Stage and a first common occurrence in the uppermost Turonian Stage was reported by Pearce et al (2003). The FO of R. fucatum in the middle Turonian Stage is described by Costa & Davey (1992) and was also recorded from the North Sea area, Norwegian Sea and West Greenland by Radmacher et al (2015), Pedersen & Nøhr-Hansen (2014) and Nøhr-Hansen et al (2016), respectively; an upper Coniacian FO was reported by Nøhr-Hansen (2012) from the Sorgenfri Formation at Kangerlussuaq, southern East Greenland.…”
Section: Aa Subzone: Senoniasphaera Rotundata (2) Newmentioning
confidence: 85%
“…5). The late Maastrichtian pollen marker species Wodehouseia spinata has not been observed in situ in NE Greenland, but is reported from upper Maastrichtian successions in southern East Greenland (Nøhr-Hansen, 2012) and in central West Greenland (Nøhr-Hansen, 1996;Pedersen & Nøhr-Hansen, 2014).…”
Section: Upper Maastrichtianmentioning
confidence: 99%
“…Dinocyst studies of Arctic Lower Cretaceous successions are relatively rare and scattered across the Canadian Arctic (Pocock, 1976;Brideaux, 1977;McIntyre & Brideaux, 1980;Davies, 1983;, Greenland (Nøhr-Hansen 1993;Pedersen & Nøhr-Hansen, 2014;Piasecki et al 2018;1694 KK Śliwińska et al…”
Section: Previous Studies Of Lower Cretaceous Boreal Dinocyst Assemblmentioning
confidence: 99%